Correlation between different levels of thyroid autoantibodies and immune checkpoint inhibitor-associated thyroid dysfunction - Jiao, Yanyan; Xu, Meihua; Rao, Xiaopang (Frontiers in Endocrinology, 2025)
BackgroundTo investigate the correlation between thyroid immune-related adverse events (irAEs) and thyroid autoantibodies in cancer patients treated with immune checkpoint inhibitors (ICIs).MethodsA retrospective analysis was conducted on 316 cancer patients (139 females, 177 males; median age 64.0 [56.0–71.0] years) treated at Qingdao Chengyang District People’s Hospital from January 2018 to December 2023. Patients were divided into a euthyroid group (n = 158) and a thyroid irAEs group (n = 158) based on the occurrence of thyroid dysfunction post-ICI therapy. The researchers received at least one treatment with ICIs, and after the initial treatment, they underwent at least one or more tests for thyroid hormone levels, TPOAb, TRAb, and TgAb, with an interval of 4 weeks or more for each test. Thyroid hormone levels and autoantibodies (TPOAb, TRAb, TgAb) were measured. Clinical characteristics and baseline thyroid autoantibodies were evaluated for their association with thyroid irAEs.ResultsThyroid irAEs included subclinical thyrotoxicosis (19.94%, n = 63), clinical thyrotoxicosis (2.53%, n = 8), subclinical hypothyroidism (6.01%, n = 19), and clinical hypothyroidism (21.52%, n = 68). Baseline thyroid autoantibodies were positive in 28.48% (n = 45) of the irAEs group versus 5.70% (n = 9) in the euthyroid group (P < 0.001). Post-ICI treatment, the thyrotoxicosis group exhibited higher TRAb titers but lower TPOAb titers and TSH levels compared to the hypothyroidism group (P < 0.05). Logistic regression identified pre-treatment TRAb positivity (OR=6.927, 95% CI: 1.817–32.724, P=0.002) and TPOAb positivity (OR = 7.128, 95% CI: 1.877–37.225, P = 0.001) as risk factors for thyroid irAEs.ConclusionPatients with malignant tumors who had high levels of TPOAb and/or TRAb before treatment were more likely to develop thyroid immune-related adverse events (irAEs) after treatment. The importance of screening for baseline thyroid autoantibodies in predicting thyroid irAEs needs to be clearly understood, and close monitoring and notification to patients should be carried out, along with prior intervention.